Scythian Weapons and Horse Harness in the Territory of Serbia - Ljuština, M.; Ninčić, I. (Археологія і давня історія України, 2017)
The article analyses the objects of Scythian origin in the territory of Serbia, which show the cultural contacts. Weapons and harness of Scythian origin in Serbia are not numerous and come mostly from burials and as accidental finds. Weapons were found in burial mounds of the Early Iron Age in the areas of Atenica, Pilatovići near Požega, and Romaja near Prizren. The finds can be traced from Vršac in the north to Prizren in the south, and the vicinity of Požega in the west. In most cases they are the items imported from the territory of traditional residence of the Scythians. На території Сербії не виявлено археологічних пам'яток, які можна однозначно інтерпретувати як скіфські. Відсутні некрополі і поселення з скіфськими елементами, проте зафіксовано предмети скіфського походження, які вказують на культурні контакти. Существующие исследования скифского горизонта в Сербии все еще не результировали открытием археологической местности, которую однозначно можно было бы охарактеризовать как скифскую. Отсутствуют некрополи и поселения со скифскими элементами, однако, зафиксировано присутствие предметов, относящихся по своему происхождению к культурным кругам скифской цивилизации, и оно указывает на соприкосновения культур. Следовательно, изучение данного культурного горизонта подразумевает в первую очередь узнавание, а также стилистический и типологический анализ данных предметов в местностях носителей другого этнического просхождения.